Pendekatan Saintific Quantum dalam Memahami Perjalanan Israâ Nabi Muhammad SAW (Teori Saintifik Modulasi Quantum Israâ) - Sadiman, Sadiman; Karolina, Asri (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2017)
Abstract This paper examined the journey of Isra Prophet Muhammad SAW with the Quantum Scientific Approach. In this paper, the theory of Israâs Quantum scientific modulation is used with deep discussion through theoretical, empirical, scientific and modulation also quantum verification. The result of this paper explained that Isra Miraj was the event of Prophet Muhammads execution in the evening which was aimed to pick up the five-hour prayer commands consisting of 17 Rakaâats according to the letter of Al-Isra [17] verse 1. This event examined our faith in God because if we use logically thinking without faith it is difficult to make a sense, furthermore, it is as wisdom for man that God, in giving orders is using the laws of cause and effect (sunatullah). Therefore, the journey of Isra performed by Prophet Muhammad SAW was accompanied by Gabriel with Buraq. Theoretically, this journey was supported by the quantum theory of light, Einsteins relativity, light wave modulation and the theory of annihilation and teleportation theory. These theories reinforce the power of Allah SWT in giving the command to his prophets is always in accordance with the nature of his irodat that prevailed in the universe. In accordance with the approach and material review with the scientific verification of the quantum, this theory is called the Israâ Quantum Modulation Theory. Although, in empirically it can be proved, but this journey remains a secret of God that cannot be solved by reason and human science, because the experiment itâs only done on electrons and protons that are very small and lifeless, whereas inanimate objects and humans it has not been able to prove, so the journey of Isra and Miraj of the Prophet Muhammad remains us a miracle that cannot be obtained by others. Keywords: Scientific, Quantum, Isra, Modulation